Study on Salicylanilide Analogue for Antioxidant Activity and Melanosis Prevention in Chinese White Shrimp (Fenneropenaeus chinensis). Issue 5 (28th May 2022) - Fang, Hua; Li, Mengyu; Chen, Hui; Chen, Jun; Hong, Zhuan; Chen, Weizhu; Fang, Meijuan
ABSTRACT: This study investigated the effects of salicylanilide analogue NBHE for shrimp preservation. The antioxidant activity of 4-Nitro-benzoic acid 3-(2-hydroxy-benzoylamino)-propyl ester (NBHE) was evaluated using the superoxide anion scavenging ability assay. The results showed that NBHE possessed a higher inhibitory effect than that of salicylic acid but weaker than that of kojic acid and ascorbic acid. The IC50 value for ascorbic acid, kojic acid, salicylic acid, and NBHE was calculated to be 9.88 ± 1.98 μg/mL, 63.10 ± 1.13 μg/mL, 328.94 ± 25.01 μg/mL, and 80.94 ± 4.20 μg/mL, respectively. The copper chelating activity of 80.04 ± 3.00% and 85.39 ± 2.97% was observed in the presence of 30 μg/mL and 35 μg/mL of NBHE, respectively. Fifty μM concentration of NBHE had no considerable cytotoxic effect in HaCaT cells. The sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) of shrimp myofibrillar proteins (MP) showed that NBHE could effectively inhibit myofibrillar protein degradation and displayed obvious preservative effect.